2003
DOI: 10.1104/pp.013094
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Starch Barley Mutant, Risø 16, Lacking the Cytosolic Small Subunit of ADP-Glucose Pyrophosphorylase, Reveals the Importance of the Cytosolic Isoform and the Identity of the Plastidial Small Subunit

Abstract: To provide information on the roles of the different forms of ADP-glucose pyrophosphorylase (AGPase) in barley (Hordeum vulgare) endosperm and the nature of the genes encoding their subunits, a mutant of barley, Risø 16, lacking cytosolic AGPase activity in the endosperm was identified. The mutation specifically abolishes the small subunit of the cytosolic AGPase and is attributable to a large deletion within the coding region of a previously characterized small subunit gene that we have called Hv.AGP.S.1. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 26 publications
(39 reference statements)
4
83
0
Order By: Relevance
“…The existence of two forms of AGPase small subunits, putative cytosolic and plastidial types, has been reported in rice (Anderson et al, 1989;Sikka et al, 2001). In the present study, we investigated the transcript level of rice type 1 AGPS (AGPS1) and type 2 AGPS (AGPS2), which encode the putative cytosolic and plastidial type small subunit, respectively (Johnson et al, 2003). The heavy application of nitrogen fertilizer enhanced slightly the mRNA level of AGPS1 in all the varieties, while it decreased the expression of AGPS2 markedly in Nipponbare and Johna (Fig.…”
Section: Expression Analysis Of Agps and Rbe Genes In The Second Leafmentioning
confidence: 85%
See 1 more Smart Citation
“…The existence of two forms of AGPase small subunits, putative cytosolic and plastidial types, has been reported in rice (Anderson et al, 1989;Sikka et al, 2001). In the present study, we investigated the transcript level of rice type 1 AGPS (AGPS1) and type 2 AGPS (AGPS2), which encode the putative cytosolic and plastidial type small subunit, respectively (Johnson et al, 2003). The heavy application of nitrogen fertilizer enhanced slightly the mRNA level of AGPS1 in all the varieties, while it decreased the expression of AGPS2 markedly in Nipponbare and Johna (Fig.…”
Section: Expression Analysis Of Agps and Rbe Genes In The Second Leafmentioning
confidence: 85%
“…One (accession number: J04960) encodes putative cytosolic type small subunit (Anderson et al, 1989), and another (accession number: AY028315) encodes putative plastidial type small subunit (Sikka et al, 2001). Johnson et al (2003) showed that AGPase small subunit genes of grass family were classfi ed into two distinct subgroups, type 1 and type 2, which consist of cDNAs encoding the cytosolic or plastidial type small subunit, respectively. In this paper, we represented tentatively the cytosolic and plastidial type small subunit genes as AGPS1 and AGPS2, respectively.…”
Section: Semi-quantitative Rt-pcr and Southern Blot Analysismentioning
confidence: 99%
“…One subunit is localized in the plastids and is the major subunit in leaves (Rö sti et al, 2006), while the other is cytosolic and contributes to starch synthesis exclusively in the endosperm (Johnson et al, 2003). A third AGP-S isoform has been described as plastidial and is localized in endosperm (Johnson et al, 2003). ADPGlc, produced by AGPase, is utilized in plastids as a Glc donor for starch synthesis by starch synthases.…”
mentioning
confidence: 99%
“…Two distinct AGP-S subunits in both barley and wheat (Triticum aestivum) arise through alternative splicing of the same gene (Thorbjørnsen et al, 1996;Burton et al, 2002b). One subunit is localized in the plastids and is the major subunit in leaves (Rö sti et al, 2006), while the other is cytosolic and contributes to starch synthesis exclusively in the endosperm (Johnson et al, 2003). A third AGP-S isoform has been described as plastidial and is localized in endosperm (Johnson et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation